Inhibition of plasma kallikrein by C1-inhibitor: role of endothelial cells and the amino-terminal domain of C1-inhibitor - Ravindran, Sriram; Grys, Thomas E.; A.Welch, Rodney; Schapira, Marc; Patston, Philip A. (Thrombosis and Haemostasis, 2004)
Activation of plasma prekallikein and generation of bradykinin are responsible for the angioedema attacks observed with C1inhibitor deficiency. Heterozygous individuals with <50% levels of active C1-inhibitor are susceptible to angioedema attacks indicating a critical need for C1-inhibitor to be present at maximum levels to prevent unwanted prekallikrein activation. Studies with purified proteins do not adequately explain this observation. Therefore to investigate why reduction of C1inhibitor to levels seen in angioedema patients results in excessive kallikrein generation we examined the effect of endothelial cells on the inhibition of kallikrein by C1-inhibitor. Surprisingly, it was found that a C1-inhibitor concentration of greater than 1 µM was needed to inhibit 3 nM kallikrein. We propose that this apparent protection from inhibition was mediated by kallikrein binding to the cells via the heavy chain in a high molecular weight kininogen and zinc independent manner. Protection of kallikrein from inhibition was not observed when C1-inhibitor truncated in the amino-terminal domain by the StcE metalloproteinase was used, which suggests a novel function for this unique domain. The requirement for high concentrations of C1-inhibitor to fully inhibit kallikrein is consistent with the fact that reduced levels of C1-inhibitor result in the kallikrein activation seen in angioedema.
Keywords: Coagulation inhibitors; proteases/inhibitors; endothelial cells; contact phase